2016
DOI: 10.1097/prs.0000000000002188
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Therapy Accelerates Axonal Regeneration, Promotes Motor Reinnervation, and Reduces Muscle Atrophy following Peripheral Nerve Injury

Abstract: In male rats, growth hormone therapy accelerates axonal regeneration, reduces muscle atrophy, and promotes muscle reinnervation. Growth hormone therapy may also maintain proliferating Schwann cells in the setting of prolonged denervation. These findings suggest potential for improved outcomes with growth hormone therapy after peripheral nerve injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
3
42
1
3
Order By: Relevance
“…Furthermore, gonadal hormones [ 129 ], like estradiol [ 130 ] and testosterone [ 131 ] contribute increasing axon regeneration after peripheral nerve section. Tuffaha et al [ 132 ] demonstrated that during GH therapy in mice, the peripheral nerve injury accelerates axonal regeneration and myelination, reduces muscle atrophy, and enhances muscle reinnervation. Neuromuscular junction analysis demonstrated a significantly greater percentage of reinnervation of motor endplates in growth hormone-treated animals compared with control.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, gonadal hormones [ 129 ], like estradiol [ 130 ] and testosterone [ 131 ] contribute increasing axon regeneration after peripheral nerve section. Tuffaha et al [ 132 ] demonstrated that during GH therapy in mice, the peripheral nerve injury accelerates axonal regeneration and myelination, reduces muscle atrophy, and enhances muscle reinnervation. Neuromuscular junction analysis demonstrated a significantly greater percentage of reinnervation of motor endplates in growth hormone-treated animals compared with control.…”
Section: Resultsmentioning
confidence: 99%
“…The femoral nerve is an alternative and suitable model for peripheral nerve injury. Crucial findings regarding nerve regeneration and neurophysiology were revealed with the help of this model (Brushart, ; Brushart, Gerber, Kessens, Chen, & Royall, ; Brushart et al, ; Irintchev et al, ; Kruspe et al, ; Madison, Archibald, & Brushart, ; Madison, Sofroniew, & Robinson, ; Meng et al, ; Robinson & Madison, ; Tuffaha et al, ). Its advantageous features, compared with the sciatic nerve model, include more feasible functional evaluation and absence of limb contractures or automutilation (Irintchev, ; Irintchev et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Apart from its effects on brain repair after an injury [ 7 , 8 , 9 , 10 , 11 , 12 ], we first reported that GH administration regenerated the transected sciatic nerve in rats [ 13 ], a finding also reported by other authors [ 14 , 15 ]. Unpublished data from our group also indicate that GH and rehabilitation improve the sensitive and motor functions of patients with SC injuries below the level of the spine, at least in ASIA (American Spinal Cord Injury Association) B and C patients [ 16 ].…”
Section: Introductionmentioning
confidence: 63%
“…We and others have demonstrated [ 13 , 14 , 15 ] in rats that early GH treatment is able to recover sciatic nerve transection, increasing the number of Schwann cells that produce myelin, promoting axonal regeneration and muscle reinnervation; consequently, the affected muscles recover their trophism. This, and our unpublished studies in patients with SC injuries [ 16 ], indicates that GH is able to promote peripheral axonal growth, and this might explain the effect of the hormone on the innervation observed in our CSR patient.…”
Section: Discussionmentioning
confidence: 99%